Representational drawing following brain injury. (October 2019) - Carson, Linda; Filipowicz, Alexandre; Anderson, Britt; Danckert, James
Abstract: Research has shown that damage to either the left or right hemisphere can lead to deficits in visuoconstructional skills including drawing and figure copying. Nevertheless, research would suggest that the nature of the deficits arising from left and right brain injury are distinct in nature if not severity, with the right hemisphere, and parietal cortex specifically, seen as critical for obtaining accurate spatial relations and the left hemisphere important for effective organisation (i.e., executive function). Much of this work on drawing and figure copying following brain damage has rested on qualitative assessments or crude marking scales with descriptive anchors for what constitutes good or poor performance. We employed quantitative analyses of drawings developed to assess accuracy in novice and expert artists. We analyzed drawings of a cube and a star in 50 patients (23, left brain damaged: LBD; 27 right brain damaged: RBD) who had suffered strokes. Our analysis was sensitive to the presence of neglect on the cube (i.e., missing left sided details) with voxel-wise lesion symptom mapping (VLSM) highlighting involvement of expected brain regions (superior temporal and supramarginal gyri). With left-sided omissions removed from analyses, we failed to find any difference between LBD and RBD patients. While the presence of left neglect appeared to exaggerate errors, this was only significant for errors of scale and proportion for the star drawing. VLSM of the distinct error domains demonstrated white matter involvement (and a minor contribution from the right insula) with respect to scale errors of the cube only. Finally, blinded judgements of hemisphere of lesion based on qualitative assessment of the drawings were no better than chance. These results suggest that figure copying is a complex task relying on large scale neural networks involving both hemispheres. Clearly, models of visuoconstructional capacity that emphasise right hemisphere dominance are not entirely accurate. Highlights: Objective, reproducible quantitative analysis of figure copying following brain injury. Metric reliably detects presence of neglect. Qualitative judgements of hemisphere of damage are unreliable. Objective metrics find no difference between left and right . Brain damaged patients.